Radial network reconfiguration and load balancing for loss minimization using genetic algorithms - Navarro, Bryan B.
The present trend in distribution regulation is to push distribution utilities to achieve high efficiency. Network-based methods to reduce losses include phase load balancing, network reconfiguration, and capacitor placement. In this paper, we minimized losses for unbalanced radial three-phase systems through the combined methods of phase load balancing and network reconfiguration. The canonical genetic algorithm was applied to the phase load balancing problem while the spanning tree-based genetic algorithm was applied to the network reconfiguration. Using a 14-bus test system, we compared five variants: balance only, reconfigure only, balance-then-reconfigure, reconfigure-then-balance, and simultaneous balance-and-reconfigure. For the 14-bus test system, the simultaneous application of phase load balancing and network reconfiguration yields the minimum losses. we also present the results of the simultaneous solutions to the IEEE 123-bus test system.